Parameter optimization of dual-pressure vaporization Kalina cycle with second evaporator parallel to economizer. (1st October 2016) - Zhu, Zilong; Zhang, Zhi; Chen, Yaping; Wu, Jiafeng
Abstract: A modified dual-pressure vaporization Kalina cycle (DPV–KC2) is proposed with the second evaporator installed parallel to the economizer and both are in series after the first evaporator. The merit is to acquire higher efficiency by reduced thermal irreversibility in heat transfer between heat source and working medium. The parameter optimizations were conducted with power recovery efficiency as the cycle performance evaluation index. The calculation conditions are set as that the inlet temperatures of heat source and cooling water are 400 °C and 25 °C respectively with the constraints such as heat transfer pinch point temperature differences are proper, the maximum evaporation pressure does not exceed 20 MPa, the vapor quality at the turbine outlet is greater than 0.85 and the exhaust temperature of heat source is not lower than 90 °C. The optimal parameters obtained include concentrations of work solution and basic solution of 0.5 and 0.3138 respectively, the evaporation dew point temperature of 300 °C, the supercool at outlet of economizer of 5 K and the superheating at the second evaporator outlet of 75 K respectively. And the corresponding power recovery efficiency of the DPV–KC2 reaches 26.4%, which is 3.4% and 15.2% respectively higher than that of the DPV–KC and the Kalina cycle. Highlights: A dual-pressure vaporization Kalina cycle is modified for reducing irreversibility. Second evaporator is parallel to economizer that in series after first evaporator. Optimal parameters were obtained for concentrations and vaporization temperatures. Calculation was under conditions of 400 °C heat source and 25 °C cooling water. Power recovery efficiency of DPV–KC2 is 26.4% that 15.2% higher than Kalina cycle.